The safety and feasibility of laparoscopic right posterior sectionectomy vs. open approach: A systematic review and meta-analysis - Mengxiao, Wang; Linkang, Xiao (Frontiers in Surgery, 2022)
Background: Laparoscopic right posterior sectionectomy (LRPS) is one of the most technically challenging and potentially hazardous procedure in laparoscopic liver resection. Although some available literatures demonstrated the safety and feasibility of LRPS, these data are limited to reports from single institution and small sample size without supporting by evidence-based medicine. So, we performed a meta-analysis to further assess the safety and feasibility comparing laparoscopic versus open right posterior sectionectomy (ORPS). Methods: MEDLINE, Embase and Cochrane Library were systematically searched for eligible studies comparing LRPS versus open approach. Random and fix effect model was used to calculate outcome measures. Results: Four studies involving a total of 541 patients were identified for inclusion: 250 in LRPS group and 291 in ORPS group. The postoperative complication and margin were not statistically different between the two groups (OR 0.49, 95% CI 0.18 to 1.35, P = 0.17), (MD 0.05, 95% CI -0.47 to 0.57, P = 0.86) respectively. LRPS had significantly longer operative time and shorter hospital stay (MD 140.32, 95% CI 16.73 to 263.91, P = 0.03), (MD -1.64, 95% CI -2.56 to -0.72, P = 0.0005) respectively. Conclusion: Data from currently available literature suggest that LRPS performed by experienced surgeon is a safe and feasible procedure in selected patient and it is associated with a reduction in hospital stay.